Weapon shape variation of male morphotypes in two freshwater prawn species genus Macrobrachium (Decapoda: Palaemonidae) - Nogueira, Caio Santos [UNESP]; Pantaleão, João Alberto Farinelli; Costa, Rogerio Caetano [UNESP] (Brill Academic Publishers, 2022)
Many animal groups can develop weapons that originate from specialized modifications in different body regions. Decapods are a classic example of organisms that develop these weapons. In this group, we can find specific appendages modified to claws that are used during agonistic conflicts, as is the case between dominant and submissive male morphotypes in freshwater prawns. Our study aimed to analyze the shape, size, and morphological integration of claw components (propodus and dactyl) in male morphotypes of two freshwater prawn congeners (Macrobrachium amazonicum and M. brasiliense). Claws of the prawns were photographed and marked with landmarks and semilandmarks for the acquisition of shape variables. The shape of the propodus and dactyl was statistically different between almost all morphotypes of the two species. The size of structures differed statistically between all morphotypes. The claws of almost all morphotypes showed a high degree of morphological integration; however, statistical differences were observed only between the morphotypes of M. brasiliense. The variation in the shape and degree of morphological integration of the claws between the morphotypes of M. amazonicum was less evident when compared to the morphotypes of M. brasiliense, which may be related to distinct patterns in the development of chelipeds of each species, that is, homochely and heterochely, respectively. Thus, the exaggerated development of a cheliped (heterochely) can cause greater variation in the shape of this structure, also influencing the degree of morphological integration between its components, as evidenced in this study.